KAPSUL EKSTRAK KULIT PISANG AMBON MENINGKATKAN KADAR NITRIT OKSIDA PADA WANITA HIPERTENSI USIA SUBUR - Ramadanti, Anisa Alfia; Wijayanti, Krisdiana; Isnawati, Muflihah (Media Penelitian dan Pengembangan Kesehatan, 2024)
Hypertension affects individuals of all ages, including women. One of the contributing factors to hypertension is oxidative stress. Banana peel contains high levels of flavonoids, which increase antioxidant activity. This study aimed to analyze the effect of ambon banana peel extract capsules on increasing nitric oxide levels and reducing blood pressure hypertensive women. This research employed quasi experimental design with purposive sampling, non randomized pre and post test control group design. The sample included 32 hypertensive women divided into two groups 16 in the intervention group and 16 in the control group. The intervention group received 2,500 mg of banana peel extract capsules addition to antihypertensive drugs, the control group received only antihypertensive drugs. Both groups were treated for 14 days. The results indicated that the mean systolic blood pressure the intervention group decreased average of 16.32 mmHg, compared to decrease of 7.49 The results indicated that the mean systolic blood pressure in the intervention group decreased an average of 16.32 mmHg, compared decrease of 7.49 mmHg in the control group. Mean diastolic blood pressure the intervention group decreased by 12.56 mmHg, compared decrease 4.68 mmHg in the control group. Nitric oxide levels increased by 61.06 points in the intervention group and decreased by 19.75 points the control group. Conclusion, the study found significant differences in pretest-posttest systolic and diastolic blood pressure between the intervention and control groups, indicating that ambon banana peel extract capsules effectively increase nitric oxide levels and reduce blood pressure in hypertensive women